Effect of rotor tip clearance on the aerodynamic performance of an aerofoil-based ducted wind turbine. (1st December 2019) - Saleem, Arslan; Kim, Man-Hoe
Graphical abstract: Highlights: Effect of rotor tip clearance on performance of an airborne wind turbine is studied. Five rotor tip clearance values (1%–5% of the shell throat radius) are considered. The wider rotor tip gap reduces the rotor thrust coefficient. The turbine power coefficient decreases with increasing rotor tip clearance. The adverse effect of rotor tip gap is more significant at the higher wind speed. Abstract: With the increase in world energy demands, the focus has been shifted toward renewable energy sources. Wind energy has been investigated as a viable source of energy in recent years and several new design concepts have been introduced to benefit from high-speed winds at higher altitudes. Buoyant airborne turbine (BAT) is a similar concept designed to exploit high altitude winds by lifting the whole wind turbine system within a toroidal shaped shell filled with helium. The present study investigates the aerodynamic performance of the BAT shell based on a NACA-9415 airfoil with different rotor blade tip clearances. Three-dimensional analysis has been conducted considering a two-bladed NREL Phase IV rotor at a variety of wind speeds for the tip gaps ranging from 1% to 5% of the shell throat radius. The influence of the blade tip clearance on the turbine performance has been explored by analysing wind turbine aerodynamic coefficients, swallowed mass flow rate and wake generated behind the wind turbine. The results showed a declining trend in the wind turbine power coefficient with the increment in tip clearance for the wind speeds of 10 m/s–20 m/s. However, at the higher wind speed, the turbine power coefficient demonstrated a direct association with the tip clearance for the tip gaps of 1%-3% followed by a drop in the turbine power coefficient at the wider tip clearance.